Pengaruh Investasi Syariah Terhadap Laju Pertumbuhan Ekonomi Di Sulawesi Selatan Periode 2018-2022 - fadriansyah, Fadriansyah; H. Idris Prakkasi; Sirajuddin (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2025)
This study aims to analyze the influence of sharia capital market investment on economic growth in South Sulawesi Province during the period 2018 to 2022. The main issue addressed is the role of sharia-compliant investments in driving regional economic growth, considering the fluctuations in Gross Regional Domestic Product (GRDP) in South Sulawesi over the observed period. Although the sharia capital market has been regulated since 2003 and offers investment instruments that comply with Islamic principles, its utilization in the context of regional economic growth has rarely been examined quantitatively. This research employs a quantitative approach using secondary data obtained from the official website of the Central Bureau of Statistics (BPS) of South Sulawesi. The findings indicate that sharia investment has a positive influence on the increase in GRDP at constant prices, which serves as a key indicator of economic growth. Data analysis shows a positive relationship between the growth of sharia investment and the region’s production capacity. Therefore, it can be concluded that the sharia capital market plays an important role in promoting economic growth and improving the welfare of society in South Sulawesi.